The Short Chain Fatty Acid Butyrate Imprints an Antimicrobial Program in Macrophages - Schulthess, Julie; Pandey, Sumeet; Capitani, Melania; Rue-Albrecht, Kevin C.; Arnold, Isabelle; Franchini, Fanny; Chomka, Agnieszka; Ilott, Nicholas E.; Johnston, Daniel G.W.; Pires, Elisabete; McCullagh, James; Sansom, Stephen N.; et al. (Immunity (Cambridge, Mass.), 2019)
Host microbial cross-talk is essential to maintain intestinal homeostasis. However, maladaptation of this response through microbial dysbiosis or defective host defense toward invasive intestinal bacteria can result in chronic inflammation. We have shown that macrophages differentiated in the presence of the bacterial metabolite butyrate display enhanced antimicrobial activity. Butyrate-induced antimicrobial activity was associated with a shift in macrophage metabolism, a reduction in mTOR kinase activity, increased LC3-associated host defense and anti-microbial peptide production in the absence of an increased inflammatory cytokine response. Butyrate drove this monocyte to macrophage differentiation program through histone deacetylase 3 (HDAC3) inhibition. Administration of butyrate induced antimicrobial activity in intestinal macrophages in vivo and increased resistance to enteropathogens. Our data suggest that (1) increased intestinal butyrate might represent a strategy to bolster host defense without tissue damaging inflammation and (2) that pharmacological HDAC3 inhibition might drive selective macrophage functions toward antimicrobial host defense. [Display omitted] •Butyrate induces differentiation of macrophages with potent antimicrobial function•Enhanced antimicrobial function is a consequence of glycolysis and mTOR inhibition•Single-cell RNA-sequencing identifies butyrate-induced antimicrobial peptides•Butyrate inhibits HDAC3 to drive metabolic changes and microbicidal function Macrophages maintain gut homeostasis by eliminating invasive pathogens and regulating inflammatory responses. Schulthess et al. demonstrate that butyrate, a bacterial fermentation product, imprints potent antimicrobial activity during macrophage differentiation through HDAC3i function.